2015
DOI: 10.1515/ejnm-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Passive and specific targeting of lymph nodes: the influence of the administration route

Abstract: Abstract:Patients diagnosed with an advanced-stage cancer present a dismal prognosis due to the presence of metastases. From the primary tumor, the cancer cells are disseminated via lymphatic circulation; metastases develop initially in lymph nodes. Therefore, the targeting of lymph nodes needs to be improved in the design of future chemotherapy, and one way to ensure this targeting is by using the subcutaneous (SC) route. Using lipid nanocapsules (LNCs) (40 nm and fluorescently-labeled with DiD) as nanocarrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…injection. 73 To test this hypothesis, we loaded a biotinylated model tissue into one of the tissue wells and injected NRho into an upstream compartment that was connected either through the pump well (well first, approximating i.v. injection) or directly through a microchannel (channel first, approximating s.c. or i.m.…”
Section: Resultsmentioning
confidence: 99%
“…injection. 73 To test this hypothesis, we loaded a biotinylated model tissue into one of the tissue wells and injected NRho into an upstream compartment that was connected either through the pump well (well first, approximating i.v. injection) or directly through a microchannel (channel first, approximating s.c. or i.m.…”
Section: Resultsmentioning
confidence: 99%
“…After changing the injection to the tumor side, we observed better tumor control in the Sal-9RE7 treatment group. This can be due to Salmonella at the tumor-draining lymph node to target migratory dendritic cells and prime T cells for tumor infiltration, 30 , 31 while direct engagement of tumor draining lymph node that develops robust anti-tumor immunity. 32 Inflammation from the initial Sal-9RE7 dose cleared within days with little adverse effect on the mice.…”
Section: Discussionmentioning
confidence: 99%
“…The greater lymphatic flow in the left side may explain the higher accumulation of nanoparticles in the left inguinal lymph node. [19] Flow cytometry revealed that the population of Cy5-positive DC was greater in the AbaLDPN-MOG group than in the LDPN-MOG group (Figure 4D; Figure S9, Supporting Information). Compared to LDPN-MOG (Figure 4E), AbaLDPN-MOG (Figure 4F) showed higher distribution throughout the lymph node.…”
Section: Lymph Node Biodistributionmentioning
confidence: 99%